Association between cardiovascular disease risk factors and occurrence of venous thromboembolism - Wattanakit, Keattiyoat; Lutsey, Pamela L.; Bell, Elizabeth J.; Gornik, Heather; Cushman, Mary; Heckbert, Susan R.; Rosamond, Wayne D.; Folsom, Aaron R. (Thrombosis and Haemostasis, 2012)
Apart from obesity, it remains controversial whether atherosclerosis and its cardiovascular risk disease (CVD) factors are associated with risk of venous thromboembolism (VTE). Using data from the Atherosclerosis Risk in Communities study (ARIC), we evaluated associations between CVD risk factors and incident VTE in a cohort of 15,340 participants who were free a history of VTE and/or anticoagulant use on enrolment. The CVD risk factors were updated during the follow-up period. Over a mean follow-up time of 15.5 years (237,375 person-years), 468 participants had VTE events. Adjusting for demographic variables and body mass index (BMI), current smokers were at greater risk [HR of 1.44 (95% CI: 1.12–1.86)] compared to non-smokers. There was a positive monotonic association between BMI and VTE risk. Individuals with a BMI ≥35 kg/m2 had a HR for VTE of 3.09 (95%CI: 2.26–4.23) compared to those with normal BMI (<25 kg/m2). Greater physical activity was associated with lower VTE risk in a demographic adjusted model; however, this association became non-significant following adjustment for BMI. Alcohol intake, diabetes, hypertension, high-density lipoprotein and low-density lipoprotein cholesterol, and triglycerides were not associated with VTE risk. In conclusion, among the well-established CVD risk factors, only current smoking and obesity were independently associated with VTE risk in this large cohort where risk factors were updated serially during follow-up. This finding corroborates that the pathogenesis of venous disease differs from that of atherosclerotic disease.
Keywords: Deep-vein thrombosis; pulmonary embolism; risk factors